1993
DOI: 10.1136/thx.48.3.264
|View full text |Cite
|
Sign up to set email alerts
|

Additive effects of exposure to silica dust and smoking on pulmonary epithelial permeability: a radioaerosol study with technetium-99m labelled DTPA.

Abstract: Background Increased pulmonary epithelial permeability evaluated by the rate of clearance from lung to blood of the radioaerosol solute technetium-99m labelled diethylenetriamine pentacetate (99Tc-DTPA) has been reported in smokers and in workers exposed to silica dust. A study was carried out to determine whether there are additive effects of cigarette smoke and exposure to silica dust on clearance rates of 9mTc-DTPA in ceramic workers. Methods Thirty one subjects with silicosis were studied, of whom 18 smoke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Mechanistic studies have demonstrated that cigarette smoke condensate significantly increases rat lung epithelial permeability, associated with a significant recruitment of neutrophils into the air‐spaces. Pulmonary epithelial permeability has also been shown to be increased in smokers when compared to non‐smokers [7]. Other studies have demonstrated increases in interleukin (IL)‐8 levels in bronchoalveolar lavage (BAL) fluid of smokers compared with that of non‐smokers [8,9], and a significant correlation between IL‐8 concentration and neutrophil count in bronchial samples of BAL fluid [9].…”
Section: Introductionmentioning
confidence: 99%
“…Mechanistic studies have demonstrated that cigarette smoke condensate significantly increases rat lung epithelial permeability, associated with a significant recruitment of neutrophils into the air‐spaces. Pulmonary epithelial permeability has also been shown to be increased in smokers when compared to non‐smokers [7]. Other studies have demonstrated increases in interleukin (IL)‐8 levels in bronchoalveolar lavage (BAL) fluid of smokers compared with that of non‐smokers [8,9], and a significant correlation between IL‐8 concentration and neutrophil count in bronchial samples of BAL fluid [9].…”
Section: Introductionmentioning
confidence: 99%
“…Acute, reversible changes in permeability probably arise through smoke-mediated release of vasoactive neuropeptides (tachykinins) [9] from sensory nerves in the airways whereas chronic increases may reflect early destruction of connective tissue in the alveoli [20][21][22]. Tars and other noxious substances in cigarette smoke increase the numbers of lung neutrophils in both symptomatic and asymptomatic smokers [23].…”
Section: Pulmonary Function In Smokers: Airway and Parenchymal Diseasementioning
confidence: 99%
“…Several years ago, smoking was considered as a risk factor for the development of silicosis in workers exposed to silica dust [ 35 ]. Even low exposure levels of respirable crystalline silica have been associated with lung cancer [ 36 ].…”
Section: Discussionmentioning
confidence: 99%